1991
DOI: 10.1083/jcb.114.4.841
|View full text |Cite
|
Sign up to set email alerts
|

Substratum-growth factor collaborations are required for the mitogenic activities of activin and FGF on embryonal carcinoma cells.

Abstract: Abstract. When P19 mouse embryonal carcinoma cells are grown in a serum-free N2 medium on surfaces of tissue culture plastic, they die within two days. The death of these P19 cells is prevented by activin A and basic FGF (bFGF) . The cells do not divide under these conditions. However, when P19 cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…These appeared to be highly transformed cells that were unable to grow on other substrates such as type IV collagen or fibronectin. It is possible that different cell types may respond differentially to substrate molecules and that this would affect their subsequent responses to growth factors, as has been suggested for the response of embryonal carcinoma cells to activin and bFGF (41). These results focus attention on the need for studies of the responses of different types of cells to cytotactin as well as on possible differences between soluble and substratum-bound cytotactin, which have been shown to have opposite effects on neurite outgrowth (38).…”
Section: Discussionmentioning
confidence: 99%
“…These appeared to be highly transformed cells that were unable to grow on other substrates such as type IV collagen or fibronectin. It is possible that different cell types may respond differentially to substrate molecules and that this would affect their subsequent responses to growth factors, as has been suggested for the response of embryonal carcinoma cells to activin and bFGF (41). These results focus attention on the need for studies of the responses of different types of cells to cytotactin as well as on possible differences between soluble and substratum-bound cytotactin, which have been shown to have opposite effects on neurite outgrowth (38).…”
Section: Discussionmentioning
confidence: 99%
“…bFGF, EGF, activin (Schubert et al, 1990;Schubert and Kimura, 1991;van den Eijnden-van Raaij et al, 1992), LIF and IL-6 have now each been shown to support the survival of P19 cells. In addition, insulin, a component of commonly used defined medium, appears to be necessary for prolonged cell survival.…”
Section: Identification Of Cntf Receptors On P19 Cellsmentioning
confidence: 96%
“…Laminin was not used because of its contribution to mitogenesis (Schubert and Kimura, 1991 for 10 min at 4"C, air-dried, dipped in radiosensitive emulsion (Kodak NTB2), exposed for autoradiography for 72 h at -7O"C, and developed. The percentage of cells with heavily labelled nuclei was then determined for 500-1500 cells in each of triplicate samples.…”
Section: Ph] Thymidine Labellingmentioning
confidence: 99%
“…Indeed, in N2 medium supplemented with 1 mg/ml BSA, P19 cells grew even in the absence of activin A, and no activin activity was observed in the BSA we used (unpublished data). Schubert and Kimura recently reported that when culture dishes were precoated with laminin or fibronectin, P19 cells grew in serum-free N2 medium (25). This suggests that precoating by one of these substances prevents components in the medium necessary for P19 cell growth from binding to culture dishes.…”
Section: Discussionmentioning
confidence: 99%